2021
DOI: 10.21273/horttech04920-21
|View full text |Cite
|
Sign up to set email alerts
|

Retail Florists Use Novel Sales Approaches during the COVID-19 Pandemic

Abstract: Retail florists in the United States were surveyed from Oct. to Nov. 2020 to document business practices and innovative approaches to marketing, designing, and delivering flowers during Mar. to Sept. 2020 of the coronavirus disease (COVID-19) pandemic. Slightly less than half of the responding florists (45.0%) closed operations for an average of 31 to 60 days (15.6%). City or county COVID-19 restrictions caused 34% to close their storefronts to customers. Nearly all offered no-contact delivery service. Approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…As a study among US florist shops showed that almost all flower shops offered no-contact delivery service due to the pandemic restrictions. Social media marketing was used by about one third of the stores as well as similar share offered no-contact shopping options [29]. It might also be interesting to research on possible changes in customer and shopping behavior after the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As a study among US florist shops showed that almost all flower shops offered no-contact delivery service due to the pandemic restrictions. Social media marketing was used by about one third of the stores as well as similar share offered no-contact shopping options [29]. It might also be interesting to research on possible changes in customer and shopping behavior after the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Menelisik pada tingginya peluang untuk mengembangkan Rawa Belong sebagai sentra penjualan bunga di Asia Tengara, dimana usaha dagang bunga seperti ini sarat dengan kreativitas tidak hanya dalam merangkai bunga namun juga dalam implementasi pemasaran dan penjualan (Chaijaroenvit et al, 2019;Chen & Huang, 2020;Etheredge & DelPrince, 2021;Febrianti et al, 2020;Huang & Chen, 2018;Kim et al, 2021;Prasetyo et al, 2020;Tanaka et al, 2019), maka pemasaran berbasis digital dirasa tepat untuk melengkapi nilai jual yang ditawarkan penjual bunga di Rawa Belong. Salah satu pemasaran digital yang dapat digunakan di Indonesia yaitu menggunakan media sosial seperti Instagram.…”
Section: Metode Pelaksanaanunclassified